Pengaruh Kedisiplinan Guru Terhadap Motivasi Belajar Peserta Didik Di Madrasah Ibtidaiyah Muhammadiyah Labakkang - Srinawati, Risna; Achmad, Fatoni (MOMENTUM : Jurnal Sosial dan Keagamaan, 2020)
This study aims to determine: 1) How is the discipline of Ibtidaiyah Muhammadiyah Labakkang Madrasah teachers, 2) How is the learning motivation of students in Madarasah Ibtidaiyah Muhammadiyah Labakkang, and 3) How is the influence of teacher discipline on the learning motivation of students in Madarasah Ibtidaiyah Muhammadiyah Labakkang. This type of research is classified as quantitative with the approach used is the ex post facto approach. The population/sample of this study is high class students. Furthermore, the data collection method used was a questionnaire. Then, the data processing and analysis techniques used are descriptive statistical analysis and statistical statistical analysis. The results obtained in this study indicate that: 1) Discipline of teachers in Muhammadiyah Labakkang Madrasah Ibtidaiyah at intervals of 61-65 which is at a frequency of 16 or 40%. 2) The students' learning motivation in Madrasah Ibtidaiyah Muhammadiyah Labakkang is at intervals of 61-65 which is at a frequency of 20 or 50%. 3) There is a significant influence of teacher discipline on student learning motivation in Madrasah Ibtidaiyah Muhammadiyah Labakkang, it can be known based on the coeeficiens table (α), the value of tcount = 6.952 is obtained. The value of ttabel can be found obtained 1,684 so comparing ttabelandtcount turns out tcount = 6.952>ttabel = 1.684, then Ho is rejected and H1 is accepted so that there is an influence between teacher discipline (x1) on learning motivation (y) in Madrasah Ibtidaiyah Muhammadiyah Labakkang.